Public Relations Strategies Via Instagram Account @Putrikarlina14 to Increase the Popularity of Garut Regional Election (Pilkada Garut) - Akmal Taufiqurrohman Ahyar; Novie Susanti Suseno; Rosanti Utami Dewi Suyatman Yatnosaputro (International Journal Labs, 2025)
This study examines the public relations strategy employed through the Instagram account @putrikarlina14 to increase the popularity of the Syakur-Putri candidate pair in the 2024 Garut regional election. The background of the study highlights the drastic rise in electability, significantly influenced by the role of social media. A descriptive qualitative method was applied, involving interviews, observations, and content analysis. The results show that communication strategies integrating personal branding and mass communication theory successfully built emotional closeness, increased engagement, and shaped a positive public image. The use of Instagram features such as Stories and Reels proved effective in reaching young voters. The study concludes that a structured digital strategy with strong visual storytelling can foster adaptive, participatory, and impactful political communication at the local level.